'My Father's Name': A Survey of Research on the Use of onoma with Respect to the Father in the Fourth Gospel. (February 2017) - Coutts, Joshua
This essay provides a survey of research for one distinctive feature of the Fourth Gospel, namely, the striking emphasis on 'name' ( onoma ) language used with reference to the Father. The small existing body of research on John's divine name concept may be situated in the context of a resurgent interest in the question of 'God' in the Fourth Gospel, and alongside broader New Testament research focused on the application of ' kyrios ' to Jesus or on the divine functions attributed to Jesus' own name. The research that has focused on John's use of the divine name may be divided into two groups: there are attempts to identify the background to John's name concept, including proposals for a Jewish hypostatic name concept, targumic tradition or the text of Isaiah; and studies which analyse John's name language have sought to locate its meaning within the context of the Gospel itself.